The Relationship Between Mental Toughness, Job Loss, and Mental Health Issues During the COVID-19 Pandemic - Mojtahedi, Dara; Dagnall, Neil; Denovan, Andrew; Clough, Peter; Hull, Sophie; Canning, Derry; Lilley, Caroline; Papageorgiou, Kostas A. (Frontiers in Psychiatry, 2021)
Concerns towards public wellbeing and mental health are increasing considering the COVID-19 pandemic’s global societal and individual impact. The present study builds on the current body of COVID-19 literature by examining the role of mental toughness (MT) in predicting negative affective states (depression, anxiety and stress) during the pandemic. The study also examined the effects of changes in employment on mental health and MT. Participants (N = 723) completed a battery of questionnaires including the Mental Toughness Questionnaire 48-item, The State-Trait Anxiety Inventory, and the Depression, Anxiety and Stress Scale – 21 items. Participants reported relatively higher levels of depression, stress and anxiety in comparison to pre-COVID-19 samples from previous research, with respondents who had lost their jobs during the pandemic reporting higher levels of negative affective states. However, mentally tough individuals appeared to report lower levels of depression, anxiety and stress. Moreover, moderation analyses identified some interaction between MT and employment status when predicting negative depression, anxiety and stress. Our findings suggest that MT may have some utility in reducing the adverse mental health effects of the pandemic on individuals however, further longitudinal research is needed to support these implications.